Impact Of Obesity on Technical Feasibility and Postoperative Outcomes of Laparoscopic Cholecystectomy - Amit H Joshi; Pratik H Vyas; Hiralkumar Rajdev; Ronak Khojani (Medsci Publications, 2016)
Introduction: Conventional abdominal surgery in grossly obese patients is associated with an increased rate of postoperative complications; thus, laparoscopic surgery may be preferred in these patients. Methods: A prospective analysis was performed of 20 obese patients who underwent laparoscopic cholecystectomy between April 2013 and April 2015 for symptomatic non-complicated gallstone disease. Technical problems at operation included difficulty with induction of pneumoperitoneum and introduction of the most lateral subcostal port, retraction of the gallbladder fundus, the need for longer instruments and the closure of the fascia. Results: Laparoscopic cholecystectomy was successfully completed in 19 patients, but one patient required conversion to open operation. There were no anaesthetic difficulties. Two patients developed minor chest infections. The mean hospital stay was 4.9 days. Conclusion: Laparoscopic cholecystectomy is feasible and can be recommended for symptomatic gallstone disease in grossly obese patients.